Study of the influence of population immunity to tick-borne encephalitis virus on the characteristics of the epidemic process in Russia - Muminov, Temur K.; Gushchin, Vladimir A.; Kleymenov, Denis A.; Tkachuk, Artem P.; Manuylov, Viktor A.; Siniavin, Andrei E.; Ogarkova, Daria A.; Kuznetsova, Nadezhda A.; Zlobin, Vladimir I.; Gintsburg, Alexander L. (Frontiers in Immunology, 2025)
BackgroundTick-borne encephalitis (TBE) is a significant public health challenge in Russia. Vaccination is one of the most effective measures to control TBE. The aim of our study was to assess the state of anti-TBE virus population immunity, including artificial post-vaccine and natural post-infection immunity, in the context of characteristics of the epidemic process in Russia.Materials and methodsDuring the period from 2018 to 2020, we studied 28,395 conditionally healthy volunteers from various regions of Russia, without age and gender restrictions. Blood serum samples were tested for anti-TBE virus IgG antibodies. All volunteers completed questionnaires to collect demographic data, information about residence, TBE vaccination, and tick bites.ResultsOur study included participants from non-endemic (Moscow and the Republic of Dagestan) and endemic regions (Moscow Region, St. Petersburg, Leningrad Region, Novosibirsk Region, Khabarovsk Region). In regions with the highest protection against TBE, such as Novosibirsk Region and Khabarovsk Region, the proportions of individuals with seropositive and protective antibody titers were below 45% and 35%, respectively. The lowest rate of protective immunity was found among children (25.4% in Novosibirsk Region and 22% in Khabarovsk Region) and those aged 60 and older (27.3% and 25.1%, respectively). Situation was even more challenging in St. Petersburg and Leningrad Region, where the rate of protective antibody titers ranged from 4.3% to 8.7%. The highest vaccination coverage was found among volunteers from Novosibirsk Region and Khabarovsk Region: 32.5% and 27.4%. In St. Petersburg and Leningrad Region, vaccination coverage was ranged from 10.4% to 11.3%, while in other regions it was below 6%. The rates of post-vaccine protective immunity were 63.1% in Khabarovsk Region, 71.6% in Novosibirsk Region and up to 50% in other regions. The rates of post-infection immunity were 33.4% in Novosibirsk Region, 42.4% in Khabarovsk Region and below 12% in other regions.ConclusionsOur results demonstrated diversity of population immunity level and structure in different regions of Russia. The analysis showed that study participants are at risk of TBE infection, especially high in endemic regions, due to insufficient level of population immunity, vaccination coverage, and protective post-vaccine immunity.